A bibliometric analysis of HER2-positive breast cancer: 1987–2024 - Ali-Thompson, Sherlissa; Daly, Gordon R.; Dowling, Gavin P.; Kilkenny, Conor; Cox, Luke; McGrath, Jason; AlRawashdeh, Ma’en M.; Naidoo, Sindhuja; Power, Colm; Hill, Arnold D. K. (Frontiers in Oncology, 2024)
Aim The overamplification of human epidermal growth factor (HER2) in breast cancer (BC) has been the subject of numerous research publications since its discovery in 1987. This is the first bibliometric analysis (BA) conducted on HER2-positive (HER2+) BC. The purpose of this BA is to analyze the published research on HER2+ BC from 1987 to 2024, highlighting the most significant scientific literature, as well as the main contributing authors and journals, and evaluating the impact of clinical and lab-based publications on HER2+ BC research. Methods The Web of Science Core Collection (WoSCC) was searched using the terms “Breast cancer” OR “Breast carcinoma” OR “Breast tumor” AND “HER2 positive” OR “HER2+”. The search was limited by publication year (1987–2024) and only full English articles were included. WoS returned 7,469 relevant results, and from this dataset, a bibliometric analysis was conducted using the “analyze results” and “journal citation report” functions in WoS and the VOSviewer 1.6.16 software to generate bibliographic coupling and co-citation analysis of authors. Results The analysis encompassed a total of 7,469 publications, revealing a notable increase in the annual number of publications, particularly in recent years. The United States, China, Italy, Germany, and Spain were the top five most prolific countries. The top five significant institutions that published HER2+ research were the University of Texas System, Unicancer, UTMD Anderson Cancer Center, Harvard University, and University of California System. Breast Cancer Research and Treatment, Clinical Cancer Research, and Clinical Breast Cancer were the top three notable journals with the highest number of HER2+ BC publications. Dennis Slamon (Nc = 45,411, H-index = 51) and Jose Baselga (Nc = 32,592, H-index = 55) were the most prolific authors. Evolving research topics include anti-HER2 therapy in the neoadjuvant setting, treatment of metastatic HER2+ BC, and overcoming therapy resistance. Conclusion This study provides an overview of HER2+ BC research published over the past three decades. It provides insight into the most cited papers and authors, and the core journals, and identifies new trends. These manuscripts have had the highest impact in the field and reflect the continued evolution of HER2 as a therapeutic target in BC.